Influence of Fluid Food Viscosity on Internal Flow Characteristics of Conveying Pump - Jia, XiaoQi; Chu, Qingyang; Zhu, ZuChao; Ding, Qiangmin; Gao, Panlong (Frontiers in Nutrition, 2022)
Fluid food conveying pump is used to convey edible or nutritional fluids and semi-fluids (containing suspended soft and hard particles and with different viscosity), such as water, glycerin, yogurt and juice concentrate. Since different fluid food has different viscosity, the internal flow characteristics and conveying performance of food conveying pump are greatly affected by viscosity. In order to obtain the influence law of fluid food viscosity on the internal flow characteristics of the pump, the internal flow characteristics of food conveying pump when conveying food of 4 different viscosity (water, glycerin, 67.2 °Bx wild jujube juice and 71.0 °Bx haw juice were compared and studied in this paper. The results showed that, with the increase of food viscosity, the overall flow loss in the pump, the entropy generation and the proportion of total entropy generation in the pump chamber increase, but the conveying performance of the food conveying pump gets worse; however, the pressure pulsation intensity caused by static and dynamic interferences decreases with the increase of viscosity.